Rekomendasi Access Point Network pada Fakultas di Lingkungan UIN Sunan Kalijaga Yogyakarta - Bambang Sugiantoro; Mahbub Puba Fawzan (JISKA (Jurnal Informatika Sunan Kalijaga), 2017)
The wireless network indoors is strongly influenced by the presence of interference. To overcome such interference and to improve the performance of wireless networks, then the optimization is done. There are several kinds of propagation that can interfere with the performance of the wireless network, which includes the number of transmitters (access point), free space loss, Received Signal Stength (RSSI), coverage that can be served, measuring attenuation at the barrier (concrete wall, soft partition, door, and floor).This research is an analysis research where the purpose of this research is to determine the position of good access point at Faculty of Shari'ah and Law Building using bayesian probability method. The first stage of this research is to determine the distance of signal reception to know the strength of the weak signal with manual random sampling so that the data obtained vary. The second stage is to determine the position of the access point with a choice of several points in order to be able to compare the best position based on the floor plan of the Faculty of Shari'ah and Law. The last stage is to calculate probability with Bayesian probability method.Result of this research is the position of the best access point on the 3rd floor that is at position B with probability value 13 while on floor 4 the best access point position at position A with value 10, position D with value 13 and position E with value 13. The most influential propagation in the Faculty of Shari'ah and Law Building is a concrete wall with a large 60% reducing the mass of radiated signals.